Ocular complications of oak processionary caterpillar setae in the Netherlands; case series, literature overview, national survey and treatment advice. Issue 4 (30th September 2020) - Tan, Matthew K. H.; Jalink, Maarten B.; Sint Jago, Naïlah F. M.; Ho, Lintje; Arnold van Vliet, J. H.; Das, Tridib; de Faber, Jan Tjeerd H. N.; Wisse, Robert P. L.
Abstract: During early summer 2019, the Netherlands experienced an outbreak of the exotic oak processionary caterpillar. The vast number of caterpillars, which live in large nests on oak trees before they turn into moths, possess thousands of small, barbed hairs (setae) that are disseminated with the wind. The hairs cause a range of primarily dermatologic problems. However, Dutch ophthalmologists started reporting patients with ophthalmologic complaints caused by the penetrating hairs of the oak processionary caterpillar. This paper focuses on the ophthalmologic complications caused by the caterpillar hairs. We collected a series of four cases with reports ranging from a corneal erosion with hairs lodged into the cornea, to a sterile endophthalmitis in which hairs were found in the vitreous. A literature review for similar cases was performed using the PubMed and Embase database. Together with the Dutch Ophthalmic Society (Nederlands Oogheelkundig Gezelschap, NOG), a national survey was issued to determine the scale of this new problem. This showed that oak processionary caterpillar related complaints are primarily limited to the south of the Netherlands. Suggested ophthalmic treatment guidelines are presented. With the next summer at the doorstep, and limited preventative measures against the caterpillar hairs, we expect a new wave of ophthalmologic complaints coming year as well.